2011
DOI: 10.5423/ppj.2011.27.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Soybean Cultivars to Cercospora sojina Isolates, the Causal Agent of Frogeye Leaf Spot in Korea

Abstract: During the summer of 2005, specimens of soybean cultivars (Daepung, Daewon, Hwanggeum and Taegwang) showing frogeye leaf spot (FLS) were obtained from various areas in Korea. Eight isolates identified as Cercospora sojina were inoculated on the adaxial leaf surfaces of 63 Korean soybean cultivars; the disease responses to each isolate were evaluated 14 days and 21 days after inoculation. Based on the disease responses (resistant or susceptible) of the cultivars by the isolates, a set of cultivars (Anpeong, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
1
8
1
Order By: Relevance
“…The activities of most of the antioxidant enzymes in the +Si-inoculated plants were enhanced to counteract the increased ROS (mainly O 2 À ) concentration via a mechanism that is most likely mediated by toxins that are released by C. sojina. Although the toxin cercosporin, typically secreted by Cercospora spp., is unknown to be produced by C. sojina (Daub et al 2013), the yellowing surrounding the lesions is considered a consequence from other C. sojina-synthesized toxins (Kim et al 2011). This fact is supported by the positive correlation between both O 2 À concentration and FLSS and O 2 À concentration and FSC found in this study.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The activities of most of the antioxidant enzymes in the +Si-inoculated plants were enhanced to counteract the increased ROS (mainly O 2 À ) concentration via a mechanism that is most likely mediated by toxins that are released by C. sojina. Although the toxin cercosporin, typically secreted by Cercospora spp., is unknown to be produced by C. sojina (Daub et al 2013), the yellowing surrounding the lesions is considered a consequence from other C. sojina-synthesized toxins (Kim et al 2011). This fact is supported by the positive correlation between both O 2 À concentration and FLSS and O 2 À concentration and FSC found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Although some studies have found that the activities of SOD and POX in soybean leaves (Shen et al 2010) and of GPX in cucumber leaves (Zhu et al 2004) increased in the presence of Si, the results of the present study are somewhat unexpected given that Si is believed to affect the plant metabolism and physiology only under stressed conditions (Epstein 1994). Nevertheless, because C. sojina is probably benefited from ROS that are generated in the necrotic tissue as a consequence of toxins secretion (Kim et al 2011), it is tempting to suggest that the Simediated lower robustness of the antioxidant system could explain why Si exacerbated soybean susceptibility to FLS.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations